2008
DOI: 10.1111/j.1365-294x.2008.04006.x
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness and social organization of coypus in the Argentinean pampas

Abstract: Behavioural and trapping studies of the social organization of coypus have suggested the occurrence of kin groups and a polygynous mating system. We used 16 microsatellite markers to analyse parentage and relatedness relationships in two populations (Jáuregui and Villa Ruiz) in the Argentinean Pampas. At Jáuregui, a dominant male monopolized most paternities, leading to a high variance in reproductive success between males and a high level of polygyny. At Villa Ruiz, variance in reproductive success was low am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
3
8
0
1
Order By: Relevance
“…No linkage disequilibria were detected between any pair of loci surveyed in the USA or Argentina by Callahan et al (2005) and also by Tunez et al (2009). In our study we observed linkage disequilibria between 6 pairs of loci (between McoD59 and McoC203 high significant (P < 0.01) linkage disequilibrium was observed) -see Table 3.…”
Section: Mcod69supporting
confidence: 41%
See 1 more Smart Citation
“…No linkage disequilibria were detected between any pair of loci surveyed in the USA or Argentina by Callahan et al (2005) and also by Tunez et al (2009). In our study we observed linkage disequilibria between 6 pairs of loci (between McoD59 and McoC203 high significant (P < 0.01) linkage disequilibrium was observed) -see Table 3.…”
Section: Mcod69supporting
confidence: 41%
“…Test for conformance to HWE in nutrias from USA and Argentina revealed that two loci (McoB17, which was analysed in our population, and McoD55) deviated from expectations after the sequential Bonferroni correction for multiple simultaneous tests (Callahan et al, 2005). In population from Argentinean Pampas Tunez et al (2009) published that 4 loci significantly (P < 0.01) deviated from expectations after Bonferroni correction.…”
Section: Mcod69mentioning
confidence: 47%
“…The values of genetic diversity were affected by the size of the nutria population; however, the genetic diversity of South Korean nutrias did not correlate with the nutria population size (R 2 = 0.0137). Nutria populations in South Korea had relatively lower levels of HO (0.298) than those from other locations, such as Louisiana, USA (0.624, 9 markers) [27]; Czech Republic (0.504, 11 markers) [39]; Maryland, USA (0.46, 27 markers) [26]; and the Argentinean Pampas (0.658, 16 markers) [53]. Furthermore, nutrias in South Korea had lower AR values (1.806) than those in other locations, such as Louisiana, USA (3.8) [27] and the Czech Republic (3.6) [39].…”
Section: Genetic Diversity Analysis Of Nutria Populationsmentioning
confidence: 94%
“…Cuando se combina esta información genética con resultados sobre comportamiento social y patrones de dispersión, se pueden describir la estructura social y la dinámica meta-poblacional, información clave para generar pautas de conservación de la fauna silvestre (Frankham et al 2002). Por ejemplo, Túnez et al (2009) utilizaron 16 marcadores microsatélite para analizar el éxito reproductivo de machos y hembras y las relaciones de parentesco entre los miembros de dos poblaciones nativas de coipo, Myocastor coypus, ubicadas en la Pampa Ondulada Bonaerense, Argentina. Los resultados obtenidos confirmaron estudios comportamentales previos (Guichón et al 2003), que sugerían una varianza elevada en el éxito reproductivo.…”
Section: H����������� �� �� �������� ��������� �� �� �������� �� ����unclassified